Perwalian Menurut Para Fuqaha (Tela'ah Kitab Fiqih Islam Wa Adillatuh, Dan Kitabun Nikah Syekh Muhammad Arsyad Al-Banjari) - Muhammad Parhan, Fathullah; Abdul Hamid; Lutfi Annisa (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This study examines the rights, conditions, and order of marriage guardianship according to the Imams of the schools of thought and jurists, with a review of the books "Fiqh Islam Wa Adillatuh" and "Kitabun Nikah" by Sheikh Muhammad Arsyad Al-Banjari. Marriage guardianship is a crucial aspect of Islamic marriage law that ensures compliance with Sharia and protects the rights of the involved parties. This study discusses the views of various schools regarding the rights and duties of guardians, as well as the conditions required for valid guardianship. By analyzing these classical literatures, this research provides a deep understanding of the guardian's role in the context of Islamic marriage and its relevance in contemporary practice. Abstrak Penelitian ini mengkaji hak, syarat, dan urutan perwalian nikah menurut para imam madzhab dan fuqaha, dengan tela'ah pada kitab "Fiqih Islam Wa Adillatuh" dan "Kitabun Nikah" karya Syekh Muhammad Arsyad Al-Banjari. Perwalian nikah adalah aspek penting dalam hukum pernikahan Islam yang memastikan kepatuhan terhadap syariah dan melindungi hak-hak pihak yang terlibat. Studi ini membahas pandangan berbagai madzhab mengenai hak dan kewajiban wali, serta kondisi yang harus dipenuhi untuk sahnya perwalian. Dengan menganalisis literatur klasik ini, penelitian ini memberikan pemahaman mendalam tentang peran wali dalam konteks pernikahan Islam dan relevansinya dalam praktik kontemporer.